A211 PROTEOLYTIC CLEAVAGE OF E-CADHERIN BY INFLAMMATORY PROTEASES PRODUCES BIOACTIVE PEPTIDES THAT MODIFY EPITHELIAL FUNCTION. (1st March 2018) - Gordon, M; MacNaughton, W
Abstract: Background: The inflammatory microenvironment in the gut contains a variety of proteases from numerous sources including inflammatory cells. We have been studying the ability of proteases to induce a switch in the colonic epithelium from a barrier to a repair phenotype (epithelial to mesenchymal transition [EMT]) characterized by increased migration and disrupted homeostasis. EMT involves the degradation of junctional proteins such as E-cadherin [Ecad], but the mechanisms by which Ecad is lost and the functional consequences of Ecad degradation remain incompletely understood. Aims: To test the hypothesis that inflammatory proteases cleave Ecad to produce peptides that alter epithelial homeostasis by altering cell migration, proliferation, or cell death. Methods: Ecad cleavage in vitro was determined using Western blot. Recombinant Ecad was incubated with neutrophil elastase [NE] in a cell-free system and 24 peptides identified by mass spectrometry were chosen for high-throughput screening based on frequency of occurrence, p-value scoring, and accessibility of cleavage sites. Peptides were synthesized and tested for biological activity including proliferation, cell death, and cell migration. Murine CMT-93 intestinal epithelial cells were cultured in 96 well plates and wounded 5 days post-confluency using the EssenBio WoundMaker™ tool. Wells were imaged simultaneously with the IncuCyte™ live-cell imaging system for 24–48 hours following exposure to 1, 10, or 100 µg/mL concentrations of peptides. Cells were transfected with a GFP marker to allow automated cell number tracking to measure proliferation. Cytotoxicity was determined using Cytotox dye which binds cells undergoing membrane degradation. All analysis was done using the IncuCyte™ ZOOM platform in conjunction with ImageJ software. Results: Basolateral stimulation of human Caco2 and murine CMT93 cells with NE confirmed the ability of NE to produce C- and N-terminal Ecad fragments in vitro. Of the 24 synthesized Ecad peptides, we identified 10 that significantly influenced wound closure rates both positively and negatively. Two peptides significantly inhibited wound healing rate by 13–26% compared to vehicle controls at a concentration of 100 µg/mL. Six peptides (100 µg/mL) significantly increased wound healing rates by 7–11% and three peptides (10 µg/mL) significantly increased wound healing rates by 6–13% compared to vehicle controls. Preliminary results suggest several of these peptides may also have cytostatic or pro-proliferative activity. Conclusions: Our results suggest that degradation of cell junction proteins by inflammatory proteases can create bioactive peptides that alter epithelial homeostasis and alter cell migration. Our data reveal a novel pathway whereby epithelia respond to inflammatory tissue damage at the cellular level to alter a barrier phenotype to a more dynamic epithelium. Funding Agencies: CIHR